Cost-effective horticultural product transportation - Wildman, Hannah (Kansas State University, 2024)
Bell Nursery is an innovative company focused on growing high quality flowers and seeing their care through retail at Home Depot. Bell is the 11th largest wholesale nursery grower in the nation. Bell’s sole focus is shipping products to Home Depot year-round. The company is owned by Central Pet and Garden, comprising thirty family farmers based mainly on the East Coast. The company focuses on reducing emissions by only shipping within three hundred miles of our distribution centers. Within the entirety of the company, they face problems daily with transportation and budgeting. From the Ohio location, they ship to 179 Home Depot stores throughout Ohio, Indiana, Michigan, Kentucky, and West Virginia. Since they currently employ only one semi-driver out of the Ohio facility, they contract loads to a company out of Grove City, Ohio. During the spring and peak season, Bell pays roughly 17 contractor drivers daily to deliver products to our stores since there are not enough company drivers. Without box trucks and semi-truck drivers, the product would not reach the stores. The roles of these drivers are important to the success of the company. If they are not getting the treatment they deserve, Bell Nursery will overall lose revenue by not providing it to our drivers. The research question we are focusing on is this: How can Bell Nursery save money by evaluating transportation choices? Using scenario analysis, the four scenarios will show that Bell Nursery should hire more employed CDL drivers and steer away from contractor drivers without looking at fringe benefits. The final scenario including the cost of fringe benefits will show the cheaper option is to continue contracting loads through an outside company.
Keywords: Agribusiness; Transportation; Logistics; Trucking; Horticulture; Sensativity analysis